Preliminary Investigations Into the Effect of Exercise-Induced Muscle Damage on Systemic Extracellular Vesicle Release in Trained Younger and Older Men - Kyriakidou, Yvoni; Cooper, Isabella; Kraev, Igor; Lange, Sigrun; Elliott, Bradley T. (Frontiers in Physiology, 2021)
Background: Exercise-induced muscle damage (EIMD) results in transient muscle inflammation, strength loss, muscle soreness and may cause subsequent exercise avoidance. Research has recently proven that skeletal muscle can also release extracellular vesicles (EVs) into the circulation following a bout of exercise. However, EV’s potential role, including as a biomarker, in the response to eccentric resistance exercise stimulus remains unclear. Methods: Twelve (younger, n = 7, 27.0 ± 1.5 years and older, n = 5, 63.0 ± 1.0 years) healthy, physically active males, undertaking moderate, regular physical activity (3-5 times per week) performed a unilateral high intensity eccentric exercise protocol. Venous plasma was collected for assessment of EVs and creatine kinase (CK) prior to EIMD, immediately after EIMD, and 1-to-72 hours post-EIMD, and maximal voluntary isometric contraction (MVIC) and delayed onset muscle soreness (DOMS) were assessed at all time points, except 1 and 2 hours post-EIMD. Results: A significant effect of both time (p = 0.005) and group (p < 0.001) was noted for MVIC, with younger participants’ MVIC being higher throughout. Whilst a significant increase was observed in DOMS in the younger group (p = 0.014) and in the older group (p = 0.034) following EIMD, no significant differences were observed between groups. CK was not different between age groups but was altered following the EIMD (main effect of time p = 0.026), with increased CK seen immediately post-, at 1 and 2 hours post-EIMD. EV count tended to be lower in older participants at rest, relative to younger participants (p = 0.056) whilst EV modal size did not differ between younger and older participants pre-EIMD. EIMD did not substantially alter EV modal size or EV count in younger or older participants, however, the alteration in EV concentration (ΔCount) and EV modal size (ΔMode) between post-EIMD and pre-EIMD negatively associated with CK activity. No significant associations were noted between MVIC or DOMS and either ΔCount or ΔMode of EVs at any time point. Conclusion: These findings suggest that profile of EV release, immediately following exercise, may predict later CK release and play a role in the EIMD response. Exercise-induced EV